New insight about Orange II elimination by characterization of spent activated carbon/Fe Fenton-like catalysts - Filipa Duarte (2013)
This work is focused on the characterization of heterogeneous Fe-based catalysts supported on activatedcarbons (ACs) that are used in elimination of the azo-dye orange II (OII) from an aqueous solution. Themain goal is to clarify the process of OII removal by analyzing textural and chemical surface properties ofthe fresh and spent activated carbon and Fenton-like catalysts upon using as adsorbents and/or catalysts.Textural changes were analyzed based on the corresponding N2 adsorption isotherms and the nature ofthe adsorbed products by TG-DTG and TPD. It was found that OII was adsorbed filling the microporositywithout degradation, although interactions between OII molecules and the AC surface groups have beendetected. The total organic carbon (TOC) removal is complete in adsorption experiments. In the catalyticexperiments using different H2O2 concentrations (in the range 6-24 mM) the TOC elimination was nevercomplete and got worse when increasing the H2O2 load. The OII molecules were partially oxidized andthe adsorption of these products also leads to some blockage of the porosity; higher blockage and higherTOC removals was noticed after experiments carried out with low H2O2 concentration. The different TOCremoval was related to the interactions of the oxidation products with the carbon surface. When usingthe highest concentration of the oxidant (24 mM), the highest biodegradability and the lowest toxicity ofthe treated solution were reached, corroborating again the different nature of the oxidation by-productsformed in each case.